Synthesis, Crystal and Supramolecular Structures of New Mononuclear Cu(II) Complex [Cu(pic)2(py)2] - Wang, P.; Ma, J.-C.; Zhao, L. (Asian Journal of Chemistry, 2015)
A new mononuclear Cu(II) complex, [Cu(pic)2(py)2] (where pic = picrate anion and py = pyridine), has been synthesized and characterized by single crystal X-ray crystallography. The crystal structure shows that Cu(II) ion has a distorted octahedral coordination geometry. The complex crystallizes in the orthorhombic crystal system with Pna 2(1), with a = 9.488(5) Å, b = 12.469(7) Å, c = 22.449(13) Å, and Z = 4. In the crystal, the short O···O contacts and hydrogen bonding interactions constitute a 2D supramolecular layer structure.